2004
DOI: 10.1021/ja0392972
|View full text |Cite
|
Sign up to set email alerts
|

A Dodecameric Porphyrin Wheel

Abstract: A dodecameric porphyrin wheel was prepared by Ag(I)-promoted intramolecular coupling of a linear porphyrin dodecamer and was observed by scanning tunneling microscopy (STM). Efficient energy hopping along the array was revealed by femtosecond transient anisotropy measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 20 publications
1
77
0
1
Order By: Relevance
“…In recent years, metal-ligand coordination has been extensively investigated by many organic chemists. 38,39,[135][136][137][138][139][140] The key to coordination-based self-assembly is the ability to manipulate the process of molecular recognition and to generate an enormous variety of rigid framework assemblies featuring well-defined nano-scale cavities. This is a considerable promising approach for the recognition and binding phase of small molecule sensing.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, metal-ligand coordination has been extensively investigated by many organic chemists. 38,39,[135][136][137][138][139][140] The key to coordination-based self-assembly is the ability to manipulate the process of molecular recognition and to generate an enormous variety of rigid framework assemblies featuring well-defined nano-scale cavities. This is a considerable promising approach for the recognition and binding phase of small molecule sensing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the hydrodynamic volumes of ring-shaped polymers are generally smaller than the corresponding linear-shaped polymers, even if the molecular weights are the same, because of the rigidity of the ring. 5,6 This should be the same in the present case. Figure 5 shows plots of KSEC vs. log MW for the mononuclear rhenium(I) complexes.…”
Section: Analysis Of Rhenium(i) Multinuclear Diimine Complexesmentioning
confidence: 66%
“…Neutral oligomers and polymers with rhenium(I) diimine, 4 platinum(II) ethynylarene 5 and metal porphyrins 6,7 as repetition units can be analyzed using gel permeation chromatography (GPC) with THF, toluene, and CH3Cl. For polynuclear metal complexes with high positive charge, however, this method cannot be used because such complexes have low solubility in solvents of low polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular cyclization of porphyrin dodecamers to a porphyrin wheel has also been achieved (Peng et al 2004). Classic examples for structural models of the photosynthetic reaction center are the cofacial bisporphyrins or bischlorins (Kalish et al 1998), which model the structural arrangement of the special pair in the reaction center (Brettar et al 2001, Pascard et al 1993, Fletcher and Therien 2002.…”
Section: Light-harvesting Complexes and Reaction Center Modelsmentioning
confidence: 99%